Harmonic Suppression in an In-Line Chebyshev Bandpass Filter by Asymmetrical Perturbations - Das, Tarun Kumar; Chatterjee, Sayan (2017 IEEE MTT-S International Microwave and RF Conference (IMaRC), 2017)
Present article provides the design of an in-line parallel-coupled Chebyshev bandpass filter centered at 5.25GHz with a fractional bandwidth of 20% for WLAN applications. The coupled-lines are modified by asymmetric rectangular perturbations subject to strong and weak coupling. The proposed filter structure exhibits second harmonic suppression of 51dB with a size reduction of 71 % and 31% compared to conventional and folded parallel-coupled lines filters respectively.